Pemikiran Filsafat Ilmu Pendidikan Rahmah El Yunusiah: Transformasi Nilai-Nilai Keislaman dalam Pendidikan Diniyyah Putri - Yusti Elida; Mukhaiyar Mukhaiyar; Resy Oktadela (Populer: Jurnal Penelitian Mahasiswa, 2024)
This study examines the philosophical thoughts of Rahmah El Yunusiah, a prominent female reformer in Islamic education in Indonesia, focusing on the transformation of Islamic values. The primary focus is on the application of Islamic values in the educational practices at Diniyyah Putri, the Islamic educational institution she founded. A qualitative approach with a literature study method was used to explore Rahmah El Yunusiah's thoughts through her works, historical documents, and institutional archives. The findings reveal that her educational philosophy emphasizes the formation of Islamic character, the development of knowledge based on tauhid, and the empowerment of Muslim women through education. The transformation of Islamic values is reflected in a holistic curriculum, the integration of religious and general sciences, and the cultivation of noble character as the foundation of education. These contributions provide new insights into the relevance of value-based Islamic education in the modern era, particularly in the context of women's education. This study recommends developing educational models that contextually adopt Islamic values to address globalization challenges.